The doctrinal background of the Qarmatian movement and its impact on Islam (Journal of the College of Basic Education, 2023)
The Qarmatians are a branch of the Ismailis politically and ideologically, as they are in fact a political sect that emanated from the Ismailis, just as the Ismaili preachers themselves have shown this sect to the world of existence, and the Qarmatians did not deviate from it except for a few of them when they entered the field of ijtihad and cited some social and political theories and demanded work With the intent of reaching the political goal they were seeking.When we talk about the Qarmati creed, it is a philosophical message that, after a long examination and a series of experiments, moved to an international call that hid goals and purposes behind it. Thought still seeks to clear its mysteries, explore its depths, and discover its essence, and there is no evidence for that from the fact that the teachings of this movement were comforting the eastern and western countries alike. It is to be embraced by all who relish its principles and teachings, regardless of region, country, gender or race.